Ecosystem approach for blue swimming crab (Portunus pelagicus) sustainability in Bekasi District, West Java, Indonesia - ERNIK YULIANA; ADI WINATA; LUDIVICA ENDANG SETIJORINI; DIARSI EKA YANI; YUNI TRI HEWINDATI; WIBOWO A. DJATMIKO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yuliana E, Winata A, Setijorini LE, Yani DE, Hewindati YT, Djatmiko WA. 2024. Ecosystem approach for blue swimming crab (Portunus pelagicus) sustainability in Bekasi District, West Java, Indonesia. Biodiversitas 25: 4117-4126. There is concern that the sustainability of blue swimming crab (BSC) (Portunus pelagicus Linnaeus 1758) resources is threatened by ever-increasing consumption. This has led to increased BSC fishing pressure, which can result in over exploitation. The study aims to analyze BSC sustainability based on the indicators of the ecosystem approach for fisheries management (EAFM) and to determine the follow-up in the form of management tactical steps. The study site was the waters of Segara Jaya Village, Taruma Jaya Sub-district, Bekasi District, West Java, Indonesia. The sampling location was the mudflats around the mangrove ecosystem. Data on BSC were collected from fishermen’s catches; the crabs’ carapace width (CW) and weight were measured, and their sex was identified. The fishermen data were collected from the entire population of Segara Jaya fishermen (40 people). We analyzed BSC sustainability using the CW-based stock assessment. The life-history parameters consisted of growth parameters, mortality, and exploitation rate estimated using the “TropFishR” package in RStudio; the rest used descriptive analysis. The results indicated that the BSC caught had an average CW of 7.25 cm (not compliant with the government policy) and an average weight of 29.24 g. There was overexploitation, with the exploitation rate value being 0.94 for males and 0.85 for females. The results of the water quality measurements were in accordance with seawater quality standards for marine biota. To properly educate fishermen, several counseling and motivational approaches are needed to build the fishermen’s awareness. Regarding fishing techniques, educating fishermen to catch BSC larger than the minimum size set by the government (CW of >10 cm) is needed. Motivation-building to fishermen so that they are invested in conserving BSC resources is also needed in the socio-economy domain.